The Effect of Chronic Rhinosinusitis on the Staging and Prognosis of Extranodal Natural Killer/T-Cell Lymphoma: A Single-Center Retrospective Analysis - Lei, Tingting; Chang, Yu; Zhang, Lei; Zhang, Mingzhi (Frontiers in Oncology, 2022)
ABSTRACT Clinically, extranodal natural killer/T-cell lymphoma (ENKTL) patients frequently had a history of chronic rhinosinusitis (CRS) before onset, and the correlation between the two diseases has not been systematically reported at present. In this study, we applied the method—retrospective analysis—to explore the relationship between CRS and ENKTL. We collected clinical data and the length of CRS history before onset in 214 patients diagnosed with ENKTL and found that the length of CRS history was correlated with the stage of 182 ENKTL patients whose primary sites were upper aerodigestive tract (UAT) (χ2 = 21.317, P = 0.046, n = 182), the Spearman Correlation Coefficient was 0.162 (P = 0.029). There was no significant difference in stage of the non-UAT-ENKTL patients (χ2 = 18.910, P = 0.091, n = 32). The COX multivariate regression analysis showed that CRS history was an independent prognostic predictor for PFS of the UAT-ENKTL patients (P = 0.004), and patients without CRS had significantly better PFS than the more than 15 years CRS history group (P = 0.001). Our founding suggested that we should not ignore the existence of chronic inflammation of the nasal cavity in ENKTL patients. And it is better to treat CRS as soon as possible in clinical practice to reduce the possibility of the occurrence or progression of UAT-ENKTL.